Landing Evaluation in Soccer Players with or without Anterior Cruciate Ligament Reconstruction - Alanazi, Ahmad; Mitchell, Katy; Roddey, Toni; Alenazi, Aqeel; Alzhrani, Msaad; Ortiz, Alexis (International Journal of Sports Medicine, 2020)
The purpose of this study was to evaluate landing biomechanics in soccer players following ACLR during two landing tasks. Eighteen soccer players with an ACLR and 18 sex-matched healthy control soccer players participated in the study. Planned landing included jumping forward and landing on the force-plates, whereas unplanned landing included jumping forward to head a soccer ball and landing on the force-plates. A significant landing×group interaction was found only for knee flexion angles (p=0.002). Follow-up comparisons showed that the ACL group landed with greater knee flexion during planned landing compared with unplanned landing (p<0.001). Significant main effects of landing were found. The unplanned landing showed reduction in hip flexion (p<0.001), hip extension moments (p<0.013), knee extension moments (p<0.001), and peak pressure (p<0.001). A significant main effect for group for gastrocnemius muscle was found showing that the ACL group landed with reduced gastrocnemius activity (p=0.002). Unplanned landing showed greater injury predisposing factors compared with planned landing. The ACL group showed nearly similar landing biomechanics to the control group during both landing tasks. However, the ACL group used a protective landing strategy by reducing gastrocnemius activity.
Keywords: soccer; landing; ACL reconstruction